2012
DOI: 10.1155/2012/928371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ant Assemblages in Three Phytophysionomies: Rocky Field, Secondary Forest, and Riparian Forest—A Case Study in the State Park of Ibitipoca, Brazil

Abstract: Ant assemblages are almost all related with the vegetation composition and so can provide us important information for conservation strategies, which are especially relevant to an environmentally protected area. We sampled the ant fauna in three different phytophysionomies in order to verify if the composition of ant species is different among the areas, especially because one of the areas is a Rocky Field and there is little information about the ant fauna in this habitat. A total of 8730 individuals were reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…Gomes et al (2010) demonstrates that ant fauna is more influenced by vegetation integrity than by fragment size, distance to edge or forest cover surrounding fragments. Lopes et al (2012) shows that the species that compose the ant assemblies in different phytophysiognomies are a reflex of the environment, especially of the plant species, supporting the hypothesis that differences in the vegetational composition result in different position of the ant assembly.…”
Section: Similarity Between Bait Types and Vegetation Physiognomiessupporting
confidence: 53%
“…Gomes et al (2010) demonstrates that ant fauna is more influenced by vegetation integrity than by fragment size, distance to edge or forest cover surrounding fragments. Lopes et al (2012) shows that the species that compose the ant assemblies in different phytophysiognomies are a reflex of the environment, especially of the plant species, supporting the hypothesis that differences in the vegetational composition result in different position of the ant assembly.…”
Section: Similarity Between Bait Types and Vegetation Physiognomiessupporting
confidence: 53%
“…Ants from the genus Camponotus are frequently found in the candeial soil and easily access trees (Rosumek, 2008). Comparing ant communities from three vegetation types in the same study area, Lopes et al (2012) found a lower number of cryptic species and a larger number of generalists in the rocky outcrops (dominated by candeia), areas that have less litter accumulation and a high number of ant genera commonly associated with plants that have extrafloral nectaries.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, there are fewer studies with ant diversity in Brazilian tropical open habitats, such as fields (but see Rosumek, 2008;Lopes et al, 2012;Viana-Silva and Jacobi, 2012). It is likely that, in these habitats, differences in species richness patterns may remain unnoticed, pointing to the need for studies on ant diversity in open habitats (Klimes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…El forrajeo y la nidificación son actividades íntimamente ligadas con la hojarasca que cubre el suelo (García-Martínez, Escobar-Sarria, López-Barrera. Castaño-Meneses, & Valenzuela-González, 2015, 2017) y la presencia de plantas con las que interactúan (Lopes et al, 2012). De esta forma, tras un impacto antropogénico como la tala de la vegetación, la compactación del suelo aumenta e influye negativamente en el establecimiento de hormigas epígeas en bosques ribereños y en la dinámica de desplazamiento de especies a escala del paisaje (García-Martínez et al, 2015.…”
unclassified